OCCURANCE OF OVARIAN ACTIVITY IN POSTPARTUM ANOESTRUS INDEGENOUS COWS OF ASSAM FOLLOWING OLFACTORY CUES AND EXOGENOUS PROGESTERONE TREATMENT - BARUAH, ANUBHA; BARUAH, K K; SARMAH, B C; BHUYAN, S; KAKOTY, B K (The Indian Journal of Animal Reproduction, 2023)
A total of 28 indigenous Assam cows at 45 days postpartum were selected and divided into 4 groups as treatment groups (A, B, C ) and control (D) consisting of 7 animals in each group. The animals in group A were isolated from the male and received daily oro nasal treatment with bull urine for 16 weeks, in group B, the cows were kept with a fertile bull and were given oronasal treatment as in group A. In group C, the cows received exogenous hormone treatment and in group D, animals were left untreated. The postpartum cows attained early onset of estrus when received treatment i.e. in groupA69.40±3.9 days (50-80 days), in group B 67.30±4.4 days (52-84 days), in group C 33.60±1.54 days (29-40 days) in comparison to group D which was 254.86±11.42 dyas (196-294 days). All treated cows exhibited sign of estrus with 100% estrus response. The duration of estrus was recorded as 21. 71±0. 92 hours (17-24 hours) in group A, 22.86±1.08 hours (18-26 hours) in group B, 26.86±1.93 hours (21-33 hours) in group C and 18. 76±0.97 hours (17-22 hours) in group D. Induction of estrus was accompanied with ovulatory response and the cows that ovulated conceived on insemination.